PREVALENSI ESCHERICHIA COLI PADA SPESIMEN URIN PENDERITA INFEKSI SALURAN KEMIH DI RSUP SANGLAH TAHUN 2019 - Arta Putra, I Putu Willy Ganang (E-Jurnal Medika Udayana, 2022)
Introduction: Urinary tract infection is the second most common infectious disease in the world with high mortality and morbidity, including in Indonesia. Escherichia coli is one of the Gram negative bacteria which often causes urinary tract infections. Urinary tract infections risks will increases as a person ages. This study is intended to determine prevalence of Escherichia coli in urine specimens of urinary tract infections at Sanglah General Hospital in 2019. Methods: The design of this0study was a descriptive observational study with a cross-sectional design that was carried out at Sanglah General Hospital in October 2020. The sample of this study came from urine samples patients with urinary tract infections at Sanglah General Hospital for the period of January - December 2019. Where the data was taken retrospectively from the register of the Clinical Microbiology Installation of Sanglah Hospital. The prevalence of Escherichia coli in urine specimens of urinary tract infections is presented in tables and graphs. Results: Most of the patients with urinary tract infections were female (53.06%). The 40-59 years age group is the age group with the most incidence of urinary tract infections (36.7%). Based on the results of urine culture urinalysis, 49 patients (81.7%) had a result of 10 5 CFU / mL which indicated a positive urinary tract infection. According to the study results, the prevalence of Escherichia coli causing urinary tract infections was 67.3%. Conclusion: Based on the research that has been done, the conclusion is that the prevalence of Escherichia coli in urine specimens of urinary tract infections at Sanglah General Hospital in 2019 was 67.3%, dominated by female patients aged 40-59 years.